Conceptualizing The Effect of Political Instability Towards Audit Committee Effectiveness and Earnings Management - Norhaziah Nawai; Nur Hidayah Laili (Euromid Academy of Business and Technology (EMABT), 2024)
This paper aims to conceptualize the relationship between audit committee (AC) characteristics and earnings management (EM). It hypothesizes that political instability moderates the relationship between the two variables. The paper bridges the knowledge gap by proposing a conceptual framework related to AC characteristics, EM, and political instability. This article reviews recent literature on CG and EM to understand how AC characteristics may mitigate EM practices. Moreover, it illustrates the effect of political instability on managers’ engagement in EM. Evidence from prior studies suggests that AC is an important part of the firm’s structure and responsible for monitoring financial information quality in financial reports. It is argued that an effective AC can reduce EM levels. During periods of intense political instability, managers are motivated to engage in high levels of EM to enhance their companies’ financial performance. This paper argues that a more effective AC will deter the opportunistic behaviors of managers to engage in EM.